Sixteen new species of Bulbophyllum section Polymeres (Orchidaceae) from New Guinea - Vermeulen, Jaap J. (Universidad de Costa Rica, 2020)
Sixteen new species of Bulbophyllum section Polymeres (Orchidaceae) from New Guinea (Papua New Guinea and Papua Province of Indonesia) are described. Four informal series in this speciose section are distinguished as an aid to identification and a key for these is provided. The sixteen species belong to two series, sharing one character: new shoots arise from a node along the rhizome or from the basal node of the pseudobulb, without being fused to it any further than the node from which they arise. The first group (with ten new species: Bulbophyllum cerastes, B. dologlossum, B. ischyron, B. nannae, B. orthoraphe, B. schistopogon, B. stagmatoglossum, B. subium, B. teinodragma, B. trivenosum) comprises plants with creeping rhizomes, the second (with six new species: Bulbophyllum farciminiferum, B. gymnothema, B. lipochilum, B. nudicaule, B. radula, B. squamiplectum) comprises plants with patent rhizomes. Key Words: Bulbophyllum section Polymeres informal series, new species, Papua New Guinea